A New Approach to Taxing Financial Intermediation Services Under a Value Added Tax - Zee, Howell (Washington, D.C. : International Monetary Fund, 2004)
This paper contains a proposal (referred to as the "modified reverse-charging" approach) to tax financial intermediation services under a VAT. At the heart of the proposal is the application of a reverse charge that shifts the collection of the VAT on deposit interest from depositors to banks, in conjunction with the establishment of a franking mechanism managed by banks that effectively transfers the VAT so collected to borrowers as credits against the VAT on their loan interest on a transaction-by-transaction basis. The proposal is fully compatible with an invoice-credit VAT and is capable of delivering the correct theoretical result at minimal administrative costs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet